Advanced RT300 Glass Fabric/Polylite Composite Laminate Simulation. (2017) - Teodorescu-Draghicescu, Horatiu; Gheorghe, Vasile; Munteanu, Renata; Szava, Ioan; Modrea, Arina
Abstract: This paper presents numerical simulations regarding the elastic properties of ten plies RT300 glass fabric laminate impregnated with Polylite 440-M888 resin subjected to off-axis loading system as well as a comparison with experimental results obtained in tensile tests on thirteen specimens. To compute the elastic properties, the glass fabric laminate may be equivalent with a new laminate with plies sequence [0/90]10 formed of unidirectional reinforced laminae. This equivalence can be considered accurate. Axial, transverse and shear moduli as well as axial-transverse Poisson ratio have been computed. The comparison between numerical simulations and experimental results obtained on "LS100 Plus" Lloyd Instruments materials testing machine show a good accordance between both types of data.